Respostas
respondido por:
15
((3^X+2) * (9^X) /243 ^(5X+1) = ((81^2X ) / ((27^(3-4X ))
[ ( 3^( X+2 ) x ( 3^2) ^X ) / ( ( 3^5 ^(5X+1 ) ] = ((3^4^(2X ) / 3 ^3( 3-4X))
3^x+2 X 3^2x/ 3^25x+5 = 3^8x / 3^ 9 -12x
X+2 + 2x - 25x - 5 = 8x -9 +12x
-22x -3 = 20x - 9
-42x = -6
x = 7
[ ( 3^( X+2 ) x ( 3^2) ^X ) / ( ( 3^5 ^(5X+1 ) ] = ((3^4^(2X ) / 3 ^3( 3-4X))
3^x+2 X 3^2x/ 3^25x+5 = 3^8x / 3^ 9 -12x
X+2 + 2x - 25x - 5 = 8x -9 +12x
-22x -3 = 20x - 9
-42x = -6
x = 7
gabisilva061106:
Espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás